An Analysis of Snoring Characteristics and Their Impact on Obstructive Sleep Apnea - Ng, Boon Han Kevin; Han, Seul A; Min, Jin-Young; Kim, Sung Wan; Min, Hye Kyu
Introduction Snoring, a common clinical features associated with OSA, has garnered notable interest due to its potential diagnostic and predictive value. About 59% of women and 78% of men snore, making it a widespread condition. The objective of the study is to investigate the impact of snoring characteristics such as snoring intensity and snoring time on the severity of obstructive sleep apnea (OSA), exploring the dynamics and potential associations between these variables and other polysomnographic parameters.